Cerebral Reorganization in Patients with Brachial Plexus Birth Injury and Residual Shoulder Problems - Björkman, Anders; Weibull, Andreas; Svensson, Hampus; Dahlin, Lars (Frontiers in Neurology, 2016)
The functional outcome after a brachial plexus birth injury (BPBI) is based on changes in the peripheral nerve and in the central nervous system. Most patients with a BPBI recover, but residual deficits in shoulder function are not uncommon. The aim of this study was to determine cerebral activation patterns in patients with BPBI and also residual symptoms from the shoulder. In seven patients (six females and one male, aged 17 – 23 years) with a BPBI and residual shoulder problems (Mallet score IV or lower), the cerebral response to active movement of the shoulder and elbow of the injured and healthy arm was monitored using functional magnetic resonance imaging (fMRI) at 3 Tesla. Movements, i.e. shoulder rotation or elbow flexion and extension, of the injured side resulted in a more pronounced and more extended activation of the contralateral primary sensorimotor cortex compared to the activation seen after moving the healthy shoulder and elbow. In addition, moving the shoulder or elbow on the injured side resulted in increased activation in ipsilateral primary sensorimotor areas an also increased activation in associated sensorimotor areas, in both hemispheres, located further posterior in the parietal lobe, which are known to be important for integration of motor tasks and spatial aspects of motor control. Thus, in this preliminary study based on a small cohort, patients with BPBI and residual shoulder problems show reorganization in sensorimotor areas in both hemispheres of the brain. The increased activation in ipsilateral sensorimotor areas and in areas that deal with both integration of motor tasks and spatial aspects of motor control in both hemispheres indicate altered dynamics between the hemispheres, which may be a cerebral compensation for the injury.